Effective management for acidic pollution in the canal network of the Mekong Delta of Vietnam: a modeling approach - Phong, N.D.; Hoanh, Chu Thai; To Phuc Tuong; Malano, H.M.M. (Elsevier, 2014)
Acidic pollution can cause severe environmental consequences annually in coastal areas overlain with acid sulfate soils (ASS). A water quality model was used as an analytical tool for exploring the effects of water management options and other interventions on acidic pollution and salinity in Bac Lieu, a coastal province of the Mekong Delta. Fifty eight percent of the provincial area is covered by ASS, and more than three-fourths (approximately 175,000 ha) are used for brackish-water shrimp culture. Simulations of acid water propagation in the canal network indicate that the combination of opening the two main sluices along the East Sea of the study area at high tide for one day every week in May and June and widening the canals that connect these sluices to the West Sea allows for adequate saline water intake and minimizes the acidic pollution in the study area. On the other hand, canal dredging in the freshwater ASS area should be done properly as it can create severe acidic pollution.